The use of modern technology by financial institutions in combating financial exclusion - Cichowicz, Ewa (Annales. Etyka w Życiu Gospodarczym, 2019)
Financial exclusion can be considered as one of the important problems in countries at the average level of socioeconomic development that include, among others, Poland. It consists in the presence of difficulties in accessing and/or using financial products and services available on the main market that meet the needs of individuals, which prevents them from leading a normal life in society. Due to its own characteristics and trends in financial markets, this phenomenon is closely linked to the issue of the digital divide. Accordingly, it can be seen that solutions leading to the reduction of financial exclusion are based on tools using information technology innovations and modern technologies. One of the methods recognised as the most effective in this area is financial education, aimed largely at children and adolescents, which additionally justifies the choice of such tools. It is equally important to determine the extent to which modern instruments are preferred in comparison with traditional ones. The aim of this paper will be the analysis of the solutions based on modern technologies that are used in actions taken to prevent financial exclusion in selected EU countries, including Poland. The structure of the paper is as follows: the first part will present the problem of financial exclusion (identifying groups particularly at risk), then a review of methods of preventing and combating financial exclusion will be presented, with particular emphasis on modern ICT tools, and the final part will indicate possible directions and barriers to the solutions that may lead to a reduced level of financial exclusion of individuals. The methods used include an in-depth analysis of the literature and a review of existing solutions which financial institutions provide on the Web.